Analysis of damage-associated molecular pattern molecules due to electroporation of cells in vitro - Polajzer, Tamara; Jarm, Tomaz; Miklavcic, Damijan (Radiology and oncology, 2020)
Tumor cells can die via immunogenic cell death pathway, in which damage-associated molecular pattern molecules (DAMPs) are released from the cells. These molecules activate cells involved in the immune response. Both innate and adaptive immune response can be activated, causing a destruction of the remaining infected cells. Activation of immune response is also an important component of tumor treatment with electrochemotherapy (ECT) and irreversible electroporation (IRE). We thus explored, if and when specific DAMPs are released as a consequence of electroporation in vitro.Materials and methods In this in vitro study, 100 μs long electric pulses were applied to a suspension of Chinese hamster ovary cells. The release of DAMPs – specifically: adenosine triphosphate (ATP), calreticulin, nucleic acids and uric acid was investigated at different time points after exposing the cells to electric pulses of different amplitudes. The release of DAMPs was statistically correlated with cell permeabilization and cell survival, e.g. reversible and irreversible electroporation.Results In general, the release of DAMPs increases with increasing pulse amplitude. Concentration of DAMPs depend on the time interval between exposure of the cells to pulses and the analysis. Concentrations of most DAMPs correlate strongly with cell death. However, we detected no uric acid in the investigated samples.Conclusions Release of DAMPs can serve as a marker for prediction of cell death. Since the stability of certain DAMPs is time dependent, this should be considered when designing protocols for detecting DAMPs after electric pulse treatment.